Louise Nevelson’s Sculpture: Influence of Modernism on the Artist’s Individuality - Zoria, Alina A. (Actual Problems of Theory and History of Art, 2014)
The article is devoted to the art of the American artist Louise Nevelson, who isn’t known in Russia for a number of reasons. Her search of original art language had been going for many years and nly in the end of the 1950’s and in the 1960’s she became a popular artist. Nevelson’s style was based on reconsideration of modernist art which she had been studying in Europe and in the USA for many years. The article considers the circle of the artists and modernist art works which inspired Nevelson during the development of her own original art language.